Investigation of retinal microcirculation alterations following carotid artery angioplasty and stenting using optical coherence tomography angiography - Shi, Zehui; Dong, Chunqiong; Tang, Hanfei; Guo, Daqiao; Li, Xianglian; Xie, Bing; Tang, Xiao; Chen, Xiuping (Frontiers in Neuroscience, 2025)
BackgroundCarotid artery stenosis (CAS) is a common vascular condition that can impair retinal and optic nerve blood supply, leading to ocular ischemic damage. Optical coherence tomography angiography (OCTA) provides a non-invasive method to evaluate retinal microcirculation and detect vascular changes in CAS patients.MethodsThis study utilized OCTA to evaluate changes in retinal microcirculation in CAS patients before and after carotid artery angioplasty and stenting. A 6 × 6 mm OCTA scan was performed to analyze deep retinal vascular complex (DVC) blood flow density, foveal avascular zone area (FAZA), foveal density within a 300 μm-wide ring surrounding the FAZ (FD-300), and radial peripapillary capillary vessel density (RPC-VD). Additionally, ultra-wide-field OCTA imaging (24 × 20 mm) was employed to comprehensively assess perfusion in both the posterior pole and peripheral retina.ResultsFollowing carotid artery angioplasty and stenting, significant improvements were observed in the ipsilateral eye, including increased macular blood flow density (p = 0.004), FD-300 (p = 0.031), RPC-VD (p = 0.028) and decreased FAZA (p = 0.018) in the deep retinal vascular layer, indicating enhanced retinal microcirculation. No statistically significant changes were found in the contralateral eye. In some cases, ultra-wide-field OCTA revealed a reduction in macular non-perfusion areas in the ipsilateral eye, alongside an increase in non-perfusion areas near the vascular arcades.ConclusionCarotid artery angioplasty and stenting effectively improves retinal microcirculation in CAS patients, as evidenced by increased blood flow density and reduced non-perfusion areas in the ipsilateral eye. OCTA is a valuable non-invasive tool for assessing retinal circulation dynamics, identifying microvascular abnormalities, and monitoring treatment efficacy in CAS patients.